2015
DOI: 10.5051/jpis.2015.45.5.162
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of buccal bone thickness of aesthetic maxillary region: a cone-beam computed tomography study

Abstract: PurposeThe aim of this study was to analyze the anatomical dimensions of the buccal bone walls of the aesthetic maxillary region for immediate implant placement, based upon cone-beam computed tomography (CBCT) scans in a sample of adult patients.MethodsTwo calibrated examiners analyzed a sample of 50 CBCT scans, performing morphometric analyses of both incisors and canines on the left and right sides. Subsequently, in the sagittal view, a line was traced through the major axis of the selected tooth. Then, a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
47
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 27 publications
3
47
1
1
Order By: Relevance
“…[13][14][15] Although many recent studies draw this same conclusion, these previous studies combine sexes for analysis, or do not differentiate between younger and older subjects. [16][17][18][19][20][21][22] The focus of this study is on sex-related and age-related differences, and hence uses an adequate sample size to identify differences between younger and older subjects of each sex. Using CBCT to resolve bone thicknesses less than 1 mm have shown questionable reliability, however, the clinical relevance of resolving this dimension is reportedly minimal.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] Although many recent studies draw this same conclusion, these previous studies combine sexes for analysis, or do not differentiate between younger and older subjects. [16][17][18][19][20][21][22] The focus of this study is on sex-related and age-related differences, and hence uses an adequate sample size to identify differences between younger and older subjects of each sex. Using CBCT to resolve bone thicknesses less than 1 mm have shown questionable reliability, however, the clinical relevance of resolving this dimension is reportedly minimal.…”
Section: Discussionmentioning
confidence: 99%
“…Cone‐beam computed tomography (CBCT) in periodontology has primarily been used for diagnostic inquiry of regional anatomy and vital structure identification in dental implant treatment 1‐6 . Historically, treatment planning decisions and risk assessment specific to alveolar bone of the natural dentition in patients requiring orthodontic tooth movement has been either intuitive and subjectively measured or determined from clinical information and two‐dimensional (2D) radiographic analyses 7,8 .…”
mentioning
confidence: 99%
“…Historically, treatment planning decisions and risk assessment specific to alveolar bone of the natural dentition in patients requiring orthodontic tooth movement has been either intuitive and subjectively measured or determined from clinical information and two‐dimensional (2D) radiographic analyses 7,8 . Unequivocally, studies have confirmed that three‐dimensional (3D) imaging allows for superior measurement accuracy of alveolar ridge height and width, a known limitation of intraoral periapical or panoramic radiographs 1‐6 . It is well recognized that traditional 2D imaging diagnostics do not allow for meaningful dentoalveolar bone risk assessment, namely of the buccal plate, prior to orthodontic tooth movement 7,8 .…”
mentioning
confidence: 99%
See 2 more Smart Citations